2020
DOI: 10.1158/1541-7786.mcr-19-0998
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0014130 Inhibits Apoptosis in Non–Small Cell Lung Cancer by Sponging miR-136-5p and Upregulating BCL2

Abstract: Previous studies indicated that circular RNAs (circRNAs) played vital roles in the development of non-small-cell lung cancer (NSCLC). Although hsa_circ_0014130 might be a potential NSCLC biomarker, its function in NSCLC remains unknown. Thus, this study aimed to investigate the role of hsa_circ_0014130 in the progression of NSCLC. The levels of hsa_circ_0014130 in NSCLC tissues and adjacent normal tissues were determined by RT-qPCR. In addition, the expressions of Bcl-2, cleaved caspase 3 in A549 cells were de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 29 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Mechanistically, circPUM1 could sponge miR-326 to promote expression of its downstream proteins, Bcl-2 and cyclin D1 (181). Furthermore, these studies also indicated that knockdown or silencing hsa_circ_0014130, circPVT1 and circPUM1 inhibited in vivo lung cancer tumorigenesis in subcutaneous xenograft mouse models (179)(180)(181).…”
Section: Signal Transducer and Activator Of Transcription (Stat) Proteinsmentioning
confidence: 88%
See 1 more Smart Citation
“…Mechanistically, circPUM1 could sponge miR-326 to promote expression of its downstream proteins, Bcl-2 and cyclin D1 (181). Furthermore, these studies also indicated that knockdown or silencing hsa_circ_0014130, circPVT1 and circPUM1 inhibited in vivo lung cancer tumorigenesis in subcutaneous xenograft mouse models (179)(180)(181).…”
Section: Signal Transducer and Activator Of Transcription (Stat) Proteinsmentioning
confidence: 88%
“…Furthermore, several researches also identified the effects of circRNAs on tumorigenesis in in vivo studies. For example, Geng et al observed that hsa_circ_0014130 had oncogenic roles in NSCLC, and functioned as a ceRNA of miR-136-5p, to activate Bcl-2 which inhibited NSCLC apoptosis ( 179 ). Qin et al showed that circPVT1 promoted NSCLC progression by regulating the miR-497/Bcl-2 axis, and inhibiting apoptosis ( 180 ).…”
Section: The Role Of Circrnas In Lung Cancermentioning
confidence: 99%
“…Several circRNAs have been found to control cell cycle events and gene expression in NSCLC by sponging miRNA [ 36 38 ]. In some instances, circRNA have acted as tumor suppressors, for instance, Hsa_circ_0002483 was found to inhibit NSCLC progression and enhance Taxol sensitivity by sponging targeting miR-182-5p [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To focus on the role of circ_0044516 in lung cancer, potential target miRNAs were predicted and miR-136 was identified. Circ_0014130 can reduce lung cancer cell apoptosis by sponging miR-136-5p and enhancing BCL2 [ 32 ]. miR-136-5p is downregulated in patients with LUSC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%